(3MGTjI LeGd Ydi GdQhVIs - (3GdNhfSGQj, LeGd GdOjf, eMeOs
(3ChdgG (B:s
(3CjVG eKd GdhLg GdSGHb jajO MSf JbOjeg aj GdLedI dG aj eKd Jdc GdYHGQI GdJj ef Mbg GdJCNjQ ajgG(B... (3hCeG bhdg(B: (3Edi UQGW GdYRjR GdMejO(B...s
(3BNQgG (B:s
(3Khdg aj cJGH GdUdGI aj GdaUd GdKGdK ajaJbQ aj GdKhGH YdjgeG(B... (3GdEjeGf GdePchQ jLH Cf jMed Ydi eLQO GdJUOjb GdLfGfjs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis